Dietary fat intake and risk of bladder cancer: Evidence from a meta-analysis of observational studies - Wang, Jian; Wang, Chuanli (Cellular and Molecular Biology, 2019)
The association between dietary fat intake and bladder cancer had been inconsistent in the previous epidemiological studies. The aim of this study was to investigate the difference between fat intake and bladder cancer risk. Databases of PubMed, Embase, and Web of Science were systematically searched for suitable studies from inception to June 2018. A meta-analysis was performed to analyze the efficacy of dietary fat intake on bladder cancer risk. A Forest plot was prepared to indicate the relationship. Ten citations were used in this study. The Funnel plot suggested highest category of dietary fat intake could increase the risk of bladder cancer (summarized relative risk (RR)= 1.279, 95% confidence interval (CI)= 1.036-1.577, I2= 53.2%, P for heterogeneity = 0.019). A positive association was found among European populations (summarized RR= 1.359, 95%CI= 1.027-1.798), but not in North American populations. The association was not significant in the subgroup analysis by fat type on bladder cancer risk. Egger test (P= 0.239) and Funnel plot showed there was no significant publication bias in the included publications. In conclusions, compared with the lowest category of dietary fat intake, the highest category could significantly increase the bladder cancer risk, especially among European populations. As some limitations existed in our analysis, large scale studies with detailed amount of dietary fat intake are needed to verify our results.